Photochromism of the complex between 40-(2-hydroxyethoxy)-7-hydroxyflavylium and b-cyclodextrin, studied by 1H NMR, UVeVis, continuous irradiation and circular dichroism - Gago, Sandra (2016)
1st International Caparica Conference on Chromogenic and Emissive Materials